Development of Unconventional Reservoirs 2020 (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The need for energy is increasing and at the same time production from the conventional reservoirs is declining quickly. This requires an economically and technically feasible source of energy for the coming years. Among some alternative future energy solutions the most approachable source is from unconventional reservoirs. As the name “unconventional” implies it requires different and challenging approach to characterize and to develop such a resource. This special issue covers some of the technical challenges for developing unconventional energy sources from shale gas/oil, tight gas sand, and coalbed methane.